DOI: 10.14264/uql.2016.987
|View full text |Cite
|
Sign up to set email alerts
|

Assessing exposure risk of arsenic, cadmium and lead (or mixed with PAHs) in soils using in-vitro methods

Abstract: There are over 150,000 contaminated sites in Australia. In most cases, soils are polluted with mixtures of contaminants, including metal/metalloids. However, current human health assessment, particularly in relation to health investigation level guidelines is based on single contaminant. If no site-specific data are available, additive effect is assumed which may overestimate or underestimate the risk. Therefore, a more detailed study on the mixture of metal/metalloids is needed. The emphasis of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 172 publications
(236 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Xia (2016) also tested mixtures of PAHs and metal/loids using the Unified BARGE Method, indicating no interaction between Cd+Pyr and Cd+B[a]P in spiked soil extracts in the simulated digestive system with regard to Cd BAC. However, Pyr and B[a]P both decreased the uptake of Cd in HepG2 cells (Xia, 2016). While, Vakharia et al (2001) using HepG2 cells observed that at 5 µM PAH concentration, the presence of various metals decreased levels of PAH-induced CYP 1A1 activity.…”
Section: Mixtures Effects Of Pahs and Metal/loidsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, Xia (2016) also tested mixtures of PAHs and metal/loids using the Unified BARGE Method, indicating no interaction between Cd+Pyr and Cd+B[a]P in spiked soil extracts in the simulated digestive system with regard to Cd BAC. However, Pyr and B[a]P both decreased the uptake of Cd in HepG2 cells (Xia, 2016). While, Vakharia et al (2001) using HepG2 cells observed that at 5 µM PAH concentration, the presence of various metals decreased levels of PAH-induced CYP 1A1 activity.…”
Section: Mixtures Effects Of Pahs and Metal/loidsmentioning
confidence: 95%
“…The UBM procedure has been used to assess contaminant bioaccessibility in soils containing both PAHs and metal/loids (Xia, 2016). In this study PAH bioaccessibility in the presence or absence of As, Cd and Pb will be assessed using different soil types.…”
Section: Bioaccessibility Measurementmentioning
confidence: 99%